ASSESSMENT & EVALUATION ON THE KNOWLEDGE, ATTITUDE & PRACTICE TOWARDS MEDICATION THERAPY MANAGEMENT AMONG COMMUNITY OF DAVANGERE CITY - ACHANKUNJU, BLESSY; THOMAS, JOBIN; Alexander, Riya; Varughese, Sheen Ann; K SAM, GLORIA (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: The prime objective of this study is to assess knowledge, attitude, and practice (KAP) toward medications in a community of Davangere city. Methods: This community-based study was conducted for 6 months using medication therapy management aspects. Ethical clearance was obtained from the Institutional Ethical Committee. Patients above 18 years of age who were willing to participate were included in the study. The data were collected using specific data collection forms, and KAP toward medications of each patient was assessed using KAP questionnaire. Medication adherence was analyzed using Morisky Medication Adherence Scale 4. Patient counseling about disease, medication, and lifestyle modification was given, and the orally taking household drugs were segregated according to class and specific clinical uses. Results: Out of 129 patients, 58.1% were male. Out of 19 diseases encountered during the study, diabetes mellitus (32.56%) and hypertension (25.58%) were most prevalent. Majority of patients (63.57%) were prescribed with cardiovascular agents. Paracetamol was found as a common household drug. Sixty-nine percent of patients were procuring medication directly from the pharmacy and the remaining 31% were procuring their medication after consulting the physician. Mean scores of KAP in basal and endpoint assessment were compared using Student's t-test. p value was found to be <0.000. Conclusion: The study tried to entitle the name of pharmacist as a patient educator who gives proper guidance to the patient and family members about the disease, domestic drug management, lifestyle modification, etc. The result of efficient patient counseling will be reflected on the proper adherence of patient toward the medication and improved quality of life. Keywords: Knowledge, attitude and practice (KAP), Medication therapy management (MTM), Morisky medication adherence Scale – 4 (MMAS-4), patient education.